Smart learning and the law: examining the case of the Dubai Judicial Institute and its inevitable transition towards a modern pedagogical paradigm - Al-Mazmi, Hind; Alzouebi, Khadeegha; Charles, Tendai (Frontiers in Education, 2025)
Traditional classroom teaching remains the primary mode of learning at the Dubai Judicial Institute (DJI), a public entity educating aspiring judiciary members and legal professionals. However, the DJI faces specific challenges in transitioning to a smart learning model, including the potential loss of valuable personal interaction, significant financial and technological requirements, and the need for staff training to adapt to new systems. Despite these hurdles, both management and learners at the DJI express readiness and enthusiasm for this paradigm shift, driven by the benefits of flexibility, time efficiency, and increased learner autonomy. This study identifies core challenges in transitioning to smart learning, highlights key andragogical practices, and evaluates the institute’s organizational readiness for change. The findings indicate that while the transition requires a phased approach and careful planning, it presents a significant opportunity to enhance judicial training. By embracing smart learning, the DJI can align with Dubai’s broader smart government initiatives, ultimately fostering a more efficient, accessible, and innovative justice system.